Self-control as a general theory of crime - Akers, Ronald L. (Journal of quantitative criminology, 1991)
Low self-control theory will have an impact on criminological theory. G&H's arguments are too forcefully and intelligently made to be ignored. I anticipate that the theory will inspire a great deal of attention and research (and much of it may be in an attempt to prove them wrong). The value of self-control theory would be advanced even more, however, if G&H would grapple with the tautology problem, attend to theoretical linkages with prior control theory, and ease off a bit from the oppositional strategy in comparing their theory with other theories.